SOWING PERFORMANCE BY A METERING MECHANISM OF CONTINUOUS FLOW IN DIFFERENT SLOPE CONDITIONS - Correia, Tiago P. da S.; Sousa, Saulo F. G. de [UNESP]; Silva, Paulo R. A. [UNESP]; Dias, Patricia P. [UNESP]; Gomes, Anderson R. A. [UNESP] (Soc Brasil Engenharia Agricola, 2016)
One of the reasons for the success of a productive culture is the correct sowing. Therefore, the seeds must be properly dosed, deposited and not damaged by the metering mechanism of the seed drill. So, the aim of this study was to evaluate in a simulator the sorghum seed deposition by a metering mechanism with continuous flow in different conditions of slope and sowing speed, and evaluate the quality of the deposited seeds assessing mechanical damage and germination. The experiment was carried out at the College of Agricultural Sciences, UNESP in Botucatu-SP, being used a simulator equipped with seed metering mechanism of helical channelled rotor type. The experimental design was randomized in a 3 x 2 factorial arrangement with six replications. The factors were three lateral slopes drill, 3%, 8% and 16%, and two sowing speed, 4 and 10 km h(-1). For the damage and germination variables we added a control treatment whose seeds were evaluated without being distributed by the metering mechanism. The results indicate that increasing the lateral slope and working speed reduce the rate of seed deposition. The metering mechanism provides mechanical damage and contributes to the reduction of seed germination.
Keywords: deposition; germination; mechanical damage; sowing